Implementasi Fatwa MUI 08/DSN-MUI/X/2016 Pada Wisata Halal Pahlawan Religi Center Di Kota Madiun - Ega Aspara Putri; Mansur Azis (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2023)
Tourism in Indonesia has been increasing lately. Tourism development is currently becoming a trend in several countries country. It is the development of sharia tourism, often called halal tourism. Provisions for halal tourist destinations are stated in the Fatwa 08/DSN-MUI/X/2016 arrange about whole activity tourism sharia. The main objective of this research is to analyze the halal tourism of the Pahlawan Religi Center from the DSN-MUI perspective. The type of study done is qualitative research with a case study of the Pahlawan Religi Center (PRC). This qualitative descriptive research is a problem-solving procedure by describes the situation based on the facts that appear as they are. The collection technique data used is the interview. The results of this study can be concluded: 1) The Pahlawan Religi Center has complied with the requirements for halal tourist destinations according to the DSN-MUI. However, this tourism has not been optimally managed regarding food and drink that must be labelled halal. 2) The supporting factors and obstacles to halal tourism at the Hero of Religion Center, according to the DSN-MUI, are influenced by the enthusiastic community and government providing facilities. 3) According to the DSN-MUI, the impact caused by the Halal Tourism of the Pahlawan Religi Center has a positive impact because it benefits the community.